2012
DOI: 10.1136/annrheumdis-2012-201766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adalimumab in patients with non-radiographic axial spondyloarthritis: results of a randomised placebo-controlled trial (ABILITY-1)

Abstract: PurposeTo evaluate the efficacy and safety of adalimumab in patients with non-radiographic axial spondyloarthritis (nr-axSpA).MethodsPatients fulfilled Assessment of Spondyloarthritis international Society (ASAS) criteria for axial spondyloarthritis, had a Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score of ≥ 4, total back pain score of ≥ 4 (10 cm visual analogue scale) and inadequate response, intolerance or contraindication to non-steroidal anti-inflammatory drugs (NSAIDs); patients fulfilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
344
3
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 470 publications
(395 citation statements)
references
References 32 publications
32
344
3
16
Order By: Relevance
“…In the Ability-1 study (18), the treatment effect of adalimumab, assessed using the end point ASAS40, was similar to that observed with etanercept after 12 weeks of treatment in the present study (38). When comparing the present study with the RAPID-axial SpA trial of certolizumab pegol treatment (20), several important differences in patient inclusion criteria and baseline demographic and disease characteristics are evident.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the Ability-1 study (18), the treatment effect of adalimumab, assessed using the end point ASAS40, was similar to that observed with etanercept after 12 weeks of treatment in the present study (38). When comparing the present study with the RAPID-axial SpA trial of certolizumab pegol treatment (20), several important differences in patient inclusion criteria and baseline demographic and disease characteristics are evident.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, several studies of anti-TNF therapy have been conducted in nonradiographic axial SpA, with results suggesting that these agents have efficacy similar to that seen in radiographic axial SpA (15)(16)(17)(18)(19)(20). However, to date the number of large well-controlled studies of treatment with anti-TNF or other biologic agents in nonradiographic axial SpA, including populations of patients satisfying current ASAS criteria for nonradiographic axial SpA, is limited.…”
mentioning
confidence: 99%
“…Safety results were similar to those obtained in adalimumab trials of polyarticular JIA 23, 24, 25 and adults with rheumatoid arthritis and SpA 26, 27, 39. No AEs were identified that were unique to patients with ERA.…”
Section: Discussionsupporting
confidence: 75%
“…Adalimumab has been previously demonstrated to be safe and effective in children ages 2–17 years with polyarticular JIA 23, 24, 25, in children ages 12–17 years with refractory juvenile ankylosing spondylitis having axial symptoms 19, and in adults with axial SpA 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial of adalimumab in 82 predominantly male AS patients, a significant decrease of 52.9% (9.3 units) in SPARCC scores of the SI joints was observed in adalimumab-treated patients after 12 weeks of therapy, whereas a decrease of only 12.7% (1.3 units) was observed in placebo-treated patients (15). In the Ability-1 Trial of adalimumab in nonradiographic axial SpA, a mean decrease of 62.7% (3.2 units) in SPARCC score for the SI joint was reported, while the placebo responses showed a decrease of 12.8% (0.6 units) (16). However, the participants in those studies were older, had a longer disease duration, and had substantially lower mean baseline SPARCC scores than the patients in the present study.…”
Section: Discussionmentioning
confidence: 95%